2001
DOI: 10.1038/35081101
|View full text |Cite
|
Sign up to set email alerts
|

Quenching quorum-sensing-dependent bacterial infection by an N-acyl homoserine lactonase

Abstract: Bacterial cells sense their population density through a sophisticated cell-cell communication system and trigger expression of particular genes when the density reaches a threshold. This type of gene regulation, which controls diverse biological functions including virulence, is known as quorum sensing. Quorum-sensing signals, such as acyl-homoserine lactones (AHLs), are the essential components of the communication system. AHLs regulate virulence gene expression in a range of plant and animal (including huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
642
0
10

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 925 publications
(659 citation statements)
references
References 28 publications
7
642
0
10
Order By: Relevance
“…Although the aiiA gene did not share significant homology with any known sequences, it did encode an HXHXD sequence motif common to metallo-␤-lactamases. Purified AiiA protein inactivated multiple AHLs in vitro (57), and biochemical analysis confirmed that AiiA functioned as a lactonase (85). Importantly, when cloned into the plant pathogen Erwinia carotovora, the aiiA gene reduced AHL release from the pathogen, decreased QS-controlled enzyme activities, and reduced soft rot disease symptoms on potato, eggplant, Chinese cabbage, carrot, and celery plants (57).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 90%
See 2 more Smart Citations
“…Although the aiiA gene did not share significant homology with any known sequences, it did encode an HXHXD sequence motif common to metallo-␤-lactamases. Purified AiiA protein inactivated multiple AHLs in vitro (57), and biochemical analysis confirmed that AiiA functioned as a lactonase (85). Importantly, when cloned into the plant pathogen Erwinia carotovora, the aiiA gene reduced AHL release from the pathogen, decreased QS-controlled enzyme activities, and reduced soft rot disease symptoms on potato, eggplant, Chinese cabbage, carrot, and celery plants (57).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 90%
“…Many transgenic plant species expressing AiiA have been shown to be more resistant to soft rot disease (85,91,92); however, the use of such plants in food production has been met with strong resistance from consumers, propelling the development of alternative quorum-quenching approaches. Bacterially mediated quorum quenching using AiiA was also demonstrated to be beneficial against plant pathogens, both when aiiA was expressed in the pathogenic bacterium itself and during coinoculation of the pathogen with bacteria naturally producing AiiA or engineered bacterial strains expressing heterologous AiiA (88,89,(93)(94)(95)(96).…”
Section: Qsi Success Storiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Production of these AHLs is hierarchically regulated in which threshold levels of 3OC12HSL are required to activate the synthesis of C4HSL [6,7]. Considerable attention has been directed at developing anti-quorum-sensing agents as possible infection control therapeutics [8][9][10]. This approach is particularly attractive in the case of P. aeruginosa because this bacterium could cause life-threatening chronic infections in the individuals with the genetic disease cystic fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…and other species [9,[12][13][14]. Genetically-modified Erwinia carotovora and Pseudomonas aeruginosa expressing AHL-lactonase showed decreased production of virulence factors and attenuated virulence [15,16]. AHL-lactonase has been over-expressed successfully in E. coli and Pichia pastoris expression system as a soluble heterologous protein [17,18].…”
Section: Introductionmentioning
confidence: 99%